Coercion and Social Support Behind Bars: Testing an Integrated Theory of Misconduct and Resistance in U.S. Prisons. (February 2015) - Day, Jacob C.; Brauer, Jonathan R.; Butler, H. Daniel
In this article, we examine key propositions from Colvin, Cullen, and Vander Ven's Differential Coercion/Social Support Theory (DCSST) to explain inmate violence, misconduct, and resistance within prison. Results from logistic regression models applied to data from a sample of 481 prisoners incarcerated in state correctional facilities across the United States provide mixed support for the theory. Coercive experiences within prison are associated with engagement in violent misconduct as well as defiant and institutionalized forms of inmate resistance. However, social support is not consistently related to either misconduct or resistance. Furthermore, results suggest that prison staff can inhibit these reactive behaviors by effectively reducing violence and promoting safety within prisons. These findings have important implications for the status of DCSST and for advancing popular explanations of inmate misconduct.